The Black Experience in America - Coombs, Norman, 1932- (Salt Lake City, UT : Project Gutenberg, 1993)
"The Black Experience in America" by Norman Coombs is a historical account written in the early 1990s. The book delves into the complex and multifaceted narratives surrounding the African American experience, tracing the journey from the African origins through slavery and into the struggles for civil rights. It seeks to illuminate the unique cultural contributions of African Americans while examining the harsh realities of racism and oppression faced throughout American history. The opening of the book sets the stage for this exploration by discussing the historical context of African origins and the beginning of slavery in America. Coombs introduces the idea of Africa as the cradle of humankind, illustrating the rich heritage that was forcibly disrupted by the transatlantic slave trade. It highlights the establishment of powerful West African empires and the subsequent dynamics of the slave trade, as well as the early economic systems that contributed to the dehumanization and commodification of African bodies in America. This foundational portion establishes a critical understanding of how the African heritage has profoundly shaped the American cultural landscape, laying the groundwork for further discussions on the diverse responses of African Americans to their circumstances. (This is an automatically generated summary.)
Release date is 1993-05-01
Keywords: African Americans -- History; Slavery -- United States -- History